2017
DOI: 10.1039/c7cp01263b
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of electronic structure methods for the determination of the ground spin states of Fe(ii), Fe(iii) and Fe(iv) complexes

Abstract: Our ability to understand and simulate the reactions catalyzed by iron depends strongly on our ability to predict the relative energetics of spin states. In this work, we studied the electronic structures of Fe ion, gaseous FeO and 14 iron complexes using Kohn-Sham density functional theory with particular focus on determining the ground spin state of these species as well as the magnitudes of relevant spin-state energy splittings. The 14 iron complexes investigated in this work have hexacoordinate geometries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 150 publications
4
124
0
Order By: Relevance
“…The M06 functional has been shown to perform well for barrier calculations on a large data set of organic reactions . However, for transition‐metal complexes, the ordering of alternative multiplicities appears reliable with B3LYP …”
Section: Computational and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M06 functional has been shown to perform well for barrier calculations on a large data set of organic reactions . However, for transition‐metal complexes, the ordering of alternative multiplicities appears reliable with B3LYP …”
Section: Computational and Experimental Detailsmentioning
confidence: 99%
“…[23] However,f or transition-metal complexes, the ordering of alternative multiplicities appears reliable with B3LYP. [24] Optimization criteria were set so that forces on any atom will be below 0.0045 a.u. and the root mean square (rms) force across all atoms will be below 0.003 a.u.…”
Section: Computational and Experimental Detailsmentioning
confidence: 99%
“…Small frequencies below 100 cm À1 were raised to 100 cm À1 in order to avoid breakdown of the rigid rotor harmonic oscillator (RRHO) model. [29] Based on ar ecent benchmark study [30] we selected the B3LYP, [31] M06-L, [32] MN15 [33] and PW6B95 [34] functionals, which performed well for the determination of the spin ground states for iron complexes, in addition to the TPSS-D3(BJ) combination. Using the geometries obtained at the TPSS-D3(BJ)/def2-TZVP level of theory single point energies were computed using al ocally modified version [28] of Gaussian 09.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The good performance of OLYP for predicting the ground spin states for these transition metal complexes is also not at all surprising, given existing literature experience. In a recent study of Fe(II), Fe(III), and Fe(IV) complexes, it was found that OLYP predicts the correct ground state in 12 out of 14 cases . Harding et al computed the enthalpy associated with conversion between the high‐ and low‐spin states of a Fe(III) spin crossover complex .…”
Section: Resultsmentioning
confidence: 99%